2019
DOI: 10.3390/ijms20184502
|View full text |Cite
|
Sign up to set email alerts
|

The Endocrine Function of Osteocalcin Regulated by Bone Resorption: A Lesson from Reduced and Increased Bone Mass Diseases

Abstract: Bone is a peculiar tissue subjected to a continuous process of self-renewal essential to assure the integrity of the skeleton and to explicate the endocrine functions. The study of bone diseases characterized by increased or reduced bone mass due to osteoclast alterations has been essential to understand the great role played by osteocalcin in the endocrine functions of the skeleton. The ability of osteoclasts to regulate the decarboxylation of osteocalcin and to control glucose metabolism, male fertility, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 81 publications
(99 reference statements)
0
27
1
Order By: Relevance
“…IL-6 plays a key role in bone metabolism, and the increase of IL-6 level leads to bone loss. This may explain the increase of Dialister flora abundance in patients with PO (Rossi et al, 2019). In addition, the abundance of Dialister decreased in patients with rheumatoid arthritis and upper motor neuron intestinal syndrome after spinal cord injury (Gungor et al, 2016;Tito et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…IL-6 plays a key role in bone metabolism, and the increase of IL-6 level leads to bone loss. This may explain the increase of Dialister flora abundance in patients with PO (Rossi et al, 2019). In addition, the abundance of Dialister decreased in patients with rheumatoid arthritis and upper motor neuron intestinal syndrome after spinal cord injury (Gungor et al, 2016;Tito et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…Across the ruffled border, protons and lysosomal degrading enzymes are transferred to the underlying bone to erode the bone matrix [ 7 ]. The secretion of protons by Vacuolar (V)-H+ATPase and Cl- by the chloride proton antiporter CLC-7 lowers the pH in the resorption lacuna to about 4.5, which leads to the demineralization of the bone matrix and unmasking the organic components mainly composed of type 1 collagen [ 8 , 9 , 10 ]. In the next step, exposed collagen and other organic components are degraded by lysosomal enzymes such as cathepsin K and MMPs (matrix metalloproteinases) released by the fusion of lysosomes with the ruffled border [ 11 , 12 , 13 ].…”
Section: Bone Remodelingmentioning
confidence: 99%
“…OCN signaling regulates the expression of genes that are associated with testosterone production in a cAMP response element binding protein (CREB)-dependent manner, as demonstrated by CREB phosphorylation in osteocalcin-treated Leydig cells and corroborated in Creb Leyding −/− mice [ 163 ]. Indeed, unOCN has been shown to activate GPRC6A using Docking simulation and in vitro assay with MA-10 and β-TC6 cell lines [ 165 ], inducing the PKA, PKC, PKG activation, as well as the Ca 2+ release [ 115 ], driving the specific expression of star , c yp11a , cyp17 , and 3 β -hsd genes that are required for testosterone biosynthesis, and representing a complex pancreas-bone-testis axis communication (reviewed in [ 162 , 166 ]). Interestingly, it was recently found that this regulation through OCN was LH independent in Sprague-Dawley male rats [ 167 ].…”
Section: The Impact Of Vitamin K In Reproductionmentioning
confidence: 99%